Long-term Outcomes of Cranioplasty: Titanium Mesh Is Not a Long-term Solution in High-risk Patients. Issue 4 (October 2018) - Kwiecien, Grzegorz J.; Rueda, Steven; Couto, Rafael A.; Hashem, Ahmed; Nagel, Sean; Schwarz, Graham S.; Zins, James E.; Gastman, Brian R.
Abstract : Background: Titanium mesh is a popular material for cranioplasty. However, long-term outcomes of these reconstructions remain unknown. We aimed to compare long-term outcomes between patients undergoing both (1) skull reconstruction with titanium mesh and other commonly used cranioplasty materials and (2) scalp reconstructions with locoregional flaps and free tissue transfers. Methods: A retrospective review of patients treated with 466 cranioplasties (401 patients) between 2002 and 2014 was performed. Results: Materials used for reconstructions included nontitanium alloplast (52.0%), titanium mesh (38%), and autologous bone (10%). Median cranial defect size was 58.4 cm 2 . Eighty-three reconstructions (18%) included full-thickness scalp defect with a median area of 155.4 cm 2 . Median follow-up was 3.9 years. Retention rate for isolated cranioplasty was 90%, 89.9%, and 77.1% for titanium mesh, nontitanium alloplast, and autologous bone, respectively ( P > 0.05). In composite defect cases, retention rate for autologous bone was comparable, 81.8% ( P > 0.05), whereas for titanium mesh and nontitanium alloplast it was significantly lower, 46.8% and 72.0%, respectively ( P < 0.05). The retention rate of titanium mesh cranioplasty with free fascio- and myocutaneous flaps was higher when compared with locoregional and free muscle flaps ( P < 0.05). Conclusions: Titanium mesh offers a durable repair of isolated bone defects. However, in high-risk patients with soft-tissue defect, the outcomes are significantly worse. In these cases, free tissue transfer for soft-tissue coverage tends to be more successful, especially when using a myocutaneous or fasciocutaneous free flap. This is the first study to identify a high complication rate of this popular material, especially when it is combined with a locoregional scalp flap or free muscle flap. Therefore, in these cases, titanium mesh should be used with caution.